New generation of polymeric wound dressings functionalized with immunoregulatory antimicrobial peptides - Felgueiras, Helena Prado (2018)
[Excerpt] Medical textiles are one of the most rapidly expanding sectors in the technical textile marketing, and wound dressing manufacture and design is possibly its most important segment. In the past, traditional dressings were used to simply manage wounds. Modern dressing technology has evolved considerably in the last 50 years and is now based on the principle of creating an optimal environment, in which accelerating wound healing, tissue regeneration, and preventing infections are the main goals. Wound dressings are among the fastest growing products in the world. In 2016 the economical burden associated with these products was estimated at ≈ 33.1 b€, increasing 5.3% over past years. Hence, the urgency for more effective, target-directed and faster solutions for both acute and chronic wound care. [...]